2015
DOI: 10.1007/s00586-015-3941-y
|View full text |Cite
|
Sign up to set email alerts
|

Which method is the most effective for preventing postoperative infection in spinal surgery?

Abstract: Our study suggests that rifamycin application to the surgical area in spinal operations with instrumentation is an effective method to prevent S. aureus infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Apart from the retrospective studies, another study carried out using living mammals demonstrated that rifampicin reduced infection (17). However, as is known, the sensitivity of human and animal tissues differs greatly, and may therefore generate misleading results.…”
Section: █ Discussionmentioning
confidence: 99%
“…Apart from the retrospective studies, another study carried out using living mammals demonstrated that rifampicin reduced infection (17). However, as is known, the sensitivity of human and animal tissues differs greatly, and may therefore generate misleading results.…”
Section: █ Discussionmentioning
confidence: 99%
“…Several rat models of infection have included lumbar vertebral osteomyelitis, implant‐associated infection, isolated discitis and external fixation colonization characterization 33‐35 33,34,36 . Titanium screws inoculated with S. aureus have been used to reproduce an implant associated infection to investigate the efficacy of antibiotic therapies 33,36 .…”
Section: Models Of Spinal Infectionsmentioning
confidence: 99%
“…33-35 10 2 -10 6 CFU of S. aureus was used as an inoculating agent in infectious models. 33,34,36 Titanium screws inoculated with S. aureus have been used to reproduce an implant associated infection to investigate the efficacy of antibiotic therapies. 33,36 In the study of pin tract bacterial migration, skin flora colonized the titanium pins in the external fixation model.…”
Section: Rodent Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus is a leading cause of infection-related morbidity and mortality [1][2][3][4] and the most common cause of postoperative infection. [5][6][7] Erythromycin, penicillin, gentamicin, and vancomycin are typically used for the treatment of S. aureus infection. However, due to the abuse of antibiotics, new multidrug-resistant strains have emerged, thus hindering the management of S. aureus.…”
Section: Introductionmentioning
confidence: 99%